Regioselectivity in metalloradical catalyzed C-H bond activation: a theoretical study - Mukherjee, Anirban; Singh, Ritesh; Mane, Kishor D.; Das, Gourab Kanti (Journal of Organometallic Chemistry, 2022)
Pure quantum mechanical calculations were performed to find out the origin of regioselectivity under the metalloradical catalysis (MRC) by Co(II)-porphyrin, which showed regioselectivity is the inherent property of the aminyl radical generated from the sulfamoyl azide substrate. Different conformational analysis for the transition state from alpha-Co-III-aminyl radical to zeta-Co-III-alkyl radical formation have been studied to find out the most stable conformation for the preferable selectivity. The outcome of our study completely agrees with the reported experimental results. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: C-H activation; DFT; Metalloporphyrin; Metalloradical; Regioselectivity